2022
DOI: 10.1097/bco.0000000000001101
|View full text |Cite
|
Sign up to set email alerts
|

How do orthopaedic surgery residency program websites feature diversity? An analysis of 187 orthopaedic surgery programs in the United States

Abstract: Background:The orthopaedic surgery residency program website represents a recruitment tool that can be used to demonstrate a program's commitment to diversity and inclusion to prospective applicants. The authors assessed how orthopaedic surgery residency programs demonstrated diversity and inclusion on their program websites and whether this varied based on National Institutes of Health (NIH) funding, top-40 medical school affiliation, university affiliation, program size, or geographic region. Methods:The aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 22 publications
1
15
1
Order By: Relevance
“…One of the elements the authors analyzed was “diversity councils,” and they found 15 (8.0%) orthopaedic residency programs included such councils. The authors also found that the average orthopaedic surgery residency program website had 4.9 ± 2.1 diversity and inclusion elements 11 , whereas our study found that 74 (38.3%) orthopaedic residencies advocated for diversity, equity, and inclusion through DEI statements.…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…One of the elements the authors analyzed was “diversity councils,” and they found 15 (8.0%) orthopaedic residency programs included such councils. The authors also found that the average orthopaedic surgery residency program website had 4.9 ± 2.1 diversity and inclusion elements 11 , whereas our study found that 74 (38.3%) orthopaedic residencies advocated for diversity, equity, and inclusion through DEI statements.…”
Section: Discussioncontrasting
confidence: 71%
“…Cohen et al evaluated 187 orthopaedic surgery residency websites for the presence of 12 elements that represented a commitment to diversity and inclusion 11 . One of the elements the authors analyzed was “diversity councils,” and they found 15 (8.0%) orthopaedic residency programs included such councils.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, female trainees placed more importance on having a mentor of the same gender than male trainees 20 . Interestingly, recently published studies investigating the commitment to diversity and inclusion on orthopaedic surgery residency websites revealed that most residency websites do not adequately promote the inclusion of gender and racial/ethnic diversity 21,22 . These reasons, among many others, are likely contributing to why orthopaedic surgery lags behind other specialties in the diversity of practicing surgeons.…”
Section: Discussionmentioning
confidence: 99%